ANALISIS PERWATAKAN TOKOH CERITA DALAM NOVEL KELING KUMANG KARYA R. MASRI SAREB PUTRA - Diana, Santi; Syam, Christanto; Seli, Sesilia (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
AbstractThis research emphasized the characterization all figures based on the characters in novel were the first elements that had characterization and character. Theories used  were novels, characterization and character. This research used descriptive methods, qualitative research forms, and a behavioral psychology approach. The source data was Keling Kumang's novel by R. Masri Sareb Putra. Data collection technique was  documentary studies. The data reflected in words, expressions, phrases and sentences contained in novel. The result of analysist are, the character of the figures in the novel there are several types of characters namely merciful (Gemuring Gading, Baji Amai, and Kumang), brave (Aryo), cheerful (Keling), abstinence surrender (Jelayan), friendly (Untai Bungai, and Bujang Sebalu), easily influenced (Entolong Cuka and Laja), vindictive (Apai Sabit), and cunning (Asam Kandis and Abang Kumang). There are two character development, namely dynamic and static. The dynamic character character development is Keling and Baji Amai, while the static character character development is Gemuring Gading, Kumang, Jelayan, Laja, Bujang Sebalu, Aryo, Entolang Cuka, Asam Kandis, Apai Sabit, Inai Abang, and Abang Kumang. The results of this study can be implemented in Indonesian Language learning in high schools in class XII students of the second semester. Keywords: Character, Disposition, Novel